Colonoscopy with polypectomy is associated with a low rate of complications in patients with cirrhosis - Huang, Robert J.; Perumpail, Ryan B.; Thosani, Nirav; Cheung, Ramsey; Friedland, Shai (Endoscopy International Open, 2016)
Background and study aims: Cirrhotic patients are at a theoretically increased risk of bleeding. The safety of polypectomy in cirrhosis is poorly defined.Patients and methods: We performed a retrospective review of patients with cirrhosis who underwent colonoscopic polypectomy at a tertiary-care hospital. Patient characteristics and polyp data were collected. Development of complications including immediate bleeding, delayed bleeding, hospitalization, blood transfusion, perforation, and death were recorded to 30-day follow-up. Clinical characteristics between bleeders and non-bleeders were compared, and predictors of bleeding were determined.Results: A total of 307 colonoscopies with 638 polypectomies were identified. Immediate bleeding occurred in 7.5 % (95 % CI 4.6 % – 10.4 %) and delayed bleeding occurred in 0.3 % (95 % CI 0.0 % – 0.9 %) of colonoscopies. All cases of immediate bleeding were controlled endoscopically and none resulted in serious complication. The rate of hospitalization was 0.7 % (95 % CI 0.0 % – 1.6 %) and repeat colonoscopy 0.3 % (95 % CI 0.0 % – 0.9 %); no cases of perforation, blood transfusion, or death occurred. Lower platelet count, higher INR, presence of ascites, and presence of esophageal varices were associated with increased risk of bleeding. Use of electrocautery was associated with a lower risk of immediate bleeding. There was no significant difference between bleeding and non-bleeding polyps with regard to size, morphology, and histology.Conclusions: Colonoscopy with polypectomy appears safe in patients with cirrhosis. There is a low risk of major complications. The risk of immediate bleeding appears higher than an average risk population; however, most bleeding is self-limited or can be controlled endoscopically. Bleeding tends to occur with more advanced liver disease. Both the sequelae of portal hypertension and coagulation abnormalities are predictive of bleeding.